Examining the effectiveness of lifelong learning programme on the learners: A way forward to policy recommendation - Kamaluddin, Megat Ahmad (University of Malaya, 2021)
In line with Vision 2020, University of Malaya has established a Centre of Continuing Education (UMCCeD) in Malaysia. UMCCeD offers Executive diploma in the areas of Management (Administration and Operations), Management (Human Resource), Management (Business), Accounting Administration, Early Childhood Education, Counselling, Information Technology, Shariah Studies and Usuluddin Studies (Al-Quran and Al-Hadith studies). The programmes are designed to enhance the skills and knowledge of the working community, career advancement and motivation towards their jobs. This study aims to explain how far the programmes have achieved their objectives and learning outcomes. A survey was conducted to understand the present status of the programmes offered at UMCCeD in the areas of programme objectives, outcomes, effectiveness and overall quality. Data from a total 2421 respondents were analysed. Results show that the programme objectives are partially achieved as some of the important objectives such as salary increase, and promotion are not at expected level. The mean value shows the high level of achieving programme outcomes and quality. There was no significant difference between male and female in terms of learning outcomes. ANOVA test shows that income level has influence on learning outcomes. Course effectiveness also significantly differ among different income groups F(n1= 4, n2= 2416), p < .05. Result shows that learning outcomes are strongly, positively and significantly correlated to programme effectiveness (r=.657, P<0.01) and programme quality (r=0.582, P<0.01). The findings can contribute to making a robust lifelong learning policy for UMCCeD and thus benefit the life-long learners. © 2021, University of Malaya. All rights reserved.